Workshop Pengenalan Cacat Las Standar Internasional di LPK Immanuel Provinsi Sumatera Utara - Sebayang, Alexander; Tarigan, Efrata; Tarigan, Liwat; Tarigan, Piktor; Bangun, Positron (INTAN CENDEKIA (Jurnal Pengabdian Masyarakat), 2023)
The Department of Mechanical Engineering of the Medan State Polytechnic (POLMED) has international standard welding practice and laboratory equipment. In line with the progress of this equipment, quite a number of teaching staff in this study program already have teaching certificates in the field of welding. The socialization of welding in this study program has received recognition from the Professional Institute International Welding (IIW) and The Welding Institute (TWI), so that the Mechanical Engineering Department has become a Competency Test Site (TUK) for IIW and TWI international certification. The proponent of this international standard welding defect recognition training program already has a CSWIP (Certificate Scheme Welding Inspection Personnel) 3.0 certificate from The Welding Institute. LPK IMMANUEL MEDAN has a Welding course training field, this is related to making vehicle frames (chassis body). Participants who take part in this program have good achievements and are prepared to enter the world of work after being declared graduated with proof of a certificate. It is very reasonable for LPK IMMANUEL MEDAN to accept the offer of an international standard welding defect identification training program held by a lecturer from the Department of Mechanical Engineering, Medan State Polytechnic (POLMED). especially to hold welding inspection socialization based on TWI standards. This knowledge will prepare prospective LPK Immanuel graduates to enter jobs in the welding field. This program is very relevant to the adult world of work. With this training, LPK participants will gain insight into how welding results meet the TWI standard, which is a standard that is widely used in the international world. This is supported by experienced and certified lecturers who carry out the service above in the CSWIP 3.0 (welding inspector) training in the use of the welding gauge which will be donated to the LPK Immanuel. Through this program, welding inspection modules and welding gauges have also been donated so that LPK participants can use them in the future